Self-sustaining and externally-powered fixed, single, and dual-axis solar trackers - A. H. Mohaimin; M. R. Uddin; A. Khalil (Institute of Advanced Engineering and Science, 2020)
Power output from a small solar panel can be affected by its power consumption when it consumes power from the solar panel. There has been a lack of proper research and experiment in the use of small solar panel with tracking systems. Its significance was detailed in this paper where the voltage output are compared with those which were externally powered. The solar trackers and a microcontroller have been designed and fabricated for this research. Due to the use of the tracking system (single axis and dual axis), the power consumption varies from one to another and its effect on the voltage output. Several experiments have been conducted and it was concluded that small solar panels are not efficient enough to utilize with tracking capabilities due to an increase in power consumption. The externally powered system was found to generate 18% more output compared to a selfsustaining system and that the increase in average power consumptions compared to a fixed panel were 31.7% and 82.5% for single-axis and dualaxis tracker respectively. A concrete evidence was made that utilizing solar tracking capabilities for low power rated solar panel is unfeasible.